Rainbow Bridge. - Hassell, Hank (Utah State University Press, 2001)
On the morning of August 14, 1909, a small, diverse group including Professor Byron Cummings of the University of Utah, Government Land Office surveyor William Douglass, pioneer archaeologist and trader John Weatherill, and Paiute guide Nasja Begay gazed at the largest structure of its kind in the world-Rainbow Bridge. Their presence marked the official discovery of the magnificent natural bridge, which spans 275 feet and towers 291 feet above the stream bed below it. Of the discovery party, only Nasja Begay had seen the stone arch before; he was one of a probably small number of Paiut.